Sphingosine 1-phosphate modulates antigen capture by murine Langerhans cells via the S1P2 receptor subtype. - Lukasz Japtok (Public Library of Science (PLoS), 2012)
Dendritic cells (DCs) play a pivotal role in the development of cutaneous contact hypersensitivity (CHS) and atopic dermatitis as they capture and process antigen and present it to T lymphocytes in the lymphoid organs. Recently, it has been indicated that a topical application of the sphingolipid sphingosine 1-phosphate (S1P) prevents the inflammatory response in CHS, but the molecular mechanism is not fully elucidated. Here we indicate that treatment of mice with S1P is connected with an impaired antigen uptake by Langerhans cells (LCs), the initial step of CHS. Most of the known actions of S1P are mediated by a family of five specific G protein-coupled receptors. Our results indicate that S1P inhibits macropinocytosis of the murine LC line XS52 via S1P(2) receptor stimulation followed by a reduced phosphatidylinositol 3-kinase (PI3K) activity. As down-regulation of S1P(2) not only diminished S1P-mediated action but also enhanced the basal activity of LCs on antigen capture, an autocrine action of S1P has been assumed. Actually, S1P is continuously produced by LCs and secreted via the ATP binding cassette transporter ABCC1 to the extracellular environment. Consequently, inhibition of ABCC1, which decreased extracellular S1P levels, markedly increased the antigen uptake by LCs. Moreover, stimulation of sphingosine kinase activity, the crucial enzyme for S1P formation, is connected not only with enhanced S1P levels but also with diminished antigen capture. These results indicate that S1P is essential in LC homeostasis and influences skin immunity. This is of importance as previous reports suggested an alteration of S1P levels in atopic skin lesions.